Diversity of Tree Species in Campus Forest of UIN Sulthan Thaha Saifuddin Jambi - Wati, Ayu Widya; Susanti, Try; Manurung, Aini Qomariah; Riany, Hesti (Universitas Labuhanbatu, 2024)
An indicator of the stability of a community within an ecosystem is diversity of species. The absence of data regarding the species diversity in the campus forest of UIN Sulthan Thaha Saifuddin Jambi prompted the conduct of this study, which aimed to identify tree types and calculate the diversity index and evenness index for the campus forest. To achieve this aim, the research site was selected through the implementation of purposive sampling, whereas the plot was determined through the utilization of systematic sampling. Aside from that, tree data was collected in 22 plots using a quadratic method with dimensions of 20 m x 20 m. The research findings revealed the acquisition of 83 tree species, comprising 30 families and a total of 464/8.62 ha individuals. The species of tree that contains the greatest number of individuals is Ixonanthes sp. The genus Ixonanthes exhibited the greatest INP, which measured 37.64%. At 3.70, the species diversity index (H') indicates a significant degree of diversity across categories. Furthermore, the evenness index (E) acquired a value of 0.84, placing it within the category of high evenness